2013
DOI: 10.3988/jcn.2013.9.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Is High IQ Protective Against Cognitive Dysfunction in Narcoleptic Patients?

Abstract: Background and PurposeThe aims of this study were to elucidate the cognitive functions of narcoleptics and determine whether intelligence protects against cognitive dysfunction and depressive mood in these patients.MethodsSixty-six subjects (33 narcoleptics, 33 controls) were administered a battery of neuropsychological tests and an individual standardized intelligence test. The cognitive functions of the narcoleptic patients and the healthy controls were compared, as were those of high-IQ and mid-to-low-IQ na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
19
1
Order By: Relevance
“…Therefore, when the influence of processing speed on fluency tasks was statistically controlled, some of these significant differences disappeared. In contrast to previous studies (Bayard et al, 2012;Delazer et al, 2011;Yoon et al, 2013;Zamarian et al, 2015), we found no significant differences in the inhibition of automatic responses. The interference index is assumed to be independent of the influence of processing speed, in contrast to commonly used tasks, where the relationship between reaction time and performance is clear (Ríos-Lago et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, when the influence of processing speed on fluency tasks was statistically controlled, some of these significant differences disappeared. In contrast to previous studies (Bayard et al, 2012;Delazer et al, 2011;Yoon et al, 2013;Zamarian et al, 2015), we found no significant differences in the inhibition of automatic responses. The interference index is assumed to be independent of the influence of processing speed, in contrast to commonly used tasks, where the relationship between reaction time and performance is clear (Ríos-Lago et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…One study in mice suggests that the loss of hypocretin is associated with visuospatial working memory deficits (Dang et al, 2018). Since this finding has not been replicated in neuropsychological studies, only one study to date has reported poor performance in the Corsi block tapping test (Yoon, Joo, Kim, Hwang, & Hong, 2013). Other studies have pointed out the relationship between hypocretin and arousal and attentional processing (Fadel & Burk, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of memory function including working memory, as well as studies of executive functions in adults with narcolepsy, have been normal in some cases, 9,11 whereas other studies have found impairments. 10,12,13,46 Patients are able to perform well during short, simple tests, but they perform less well on longer or more demanding tests because a higher proportion of cognitive resources are recruited for the maintenance of alertness. 47 The patients with comorbid psychiatric disorders had a significantly lower FSIQ than the group without comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients with narcolepsy may attain high performance in several neuropsychological domains, but, at the same time, they can have difficulty in areas such as working memory, executive function, reward processing, and decision making. [10][11][12][13] Although most patients with narcolepsy experience the onset of symptoms in childhood or adolescence, comparatively few studies have focused on aspects of the disease before adulthood and very few studies have addressed the psychiatric and cognitive consequences in childhood. Several retrospective hospital-based studies have described poor school performance in a large proportion of children with narcolepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies suggested that while patients may attain high performances in several neuropsychological subdomains, they can have difficulties in areas such as working memory, executive functioning, reward processing, and decision making [ 11 , 12 , 13 ]. In adults with narcolepsy with cataplexy, attention and executive disorders, especially for long and complex cognitive tasks, have been reported [ 12 , 14 , 15 , 16 , 17 , 18 ] with a deleterious impact on quality of life.…”
Section: Introductionmentioning
confidence: 99%